Profiles of sleep changes during the COVID‐19 pandemic: Demographic, behavioural and psychological factors. (17th November 2020) - Robillard, Rebecca; Dion, Karianne; Pennestri, Marie‐Helene; Solomonova, Elizaveta; Lee, Elliott; Saad, Mysa; Murkar, Anthony; Godbout, Roger; Edwards, Jodi D.; Quilty, Lena; Daros, Alexander R.; Bhatla, Raj; et al.
Summary: This study aimed to evaluate changes in sleep during the COVID‐19 outbreak, and used data‐driven approaches to identify distinct profiles of changes in sleep‐related behaviours. Demographic, behavioural and psychological factors associated with sleep changes were also investigated. An online population survey assessing sleep and mental health was distributed between 3 April and 24 June 2020. Retrospective questions were used to estimate temporal changes from before to during the outbreak. In 5, 525 Canadian respondents (67.1% females, 16–95 years old: Mean ±  SD  = 55.6 ± 16.3 years), wake‐up times were significantly delayed relative to pre‐outbreak estimates ( p <  .001, η p 2  = 0.04). Occurrences of clinically meaningful sleep difficulties significantly increased from 36.0% before the outbreak to 50.5% during the outbreak (all p <  .001, g  ≥ 0.27). Three subgroups with distinct profiles of changes in sleep behaviours were identified: "Reduced Time in Bed", "Delayed Sleep" and "Extended Time in Bed". The "Reduced Time in Bed" and "Delayed Sleep" subgroups had more adverse sleep outcomes and psychological changes during the outbreak. The emergence of new sleep difficulties was independently associated with female sex, chronic illnesses, being employed, family responsibilities, earlier wake‐up times, higher stress levels, as well as heavier alcohol use and television exposure. The heterogeneity of sleep changes in response to the pandemic highlights the need for tailored interventions to address sleep problems.